Guide to Information technology - "Syed ,Shakil Ahmed" (Delhi, 2004)
India's future road map will be dominated by the plans of e-governance. Knowledge is body's monopoly and now through the media of Internet, an invention of a new idea of discovery at a distant corner of the globe can be made available at the finger-tips of persons all over the world.
Keywords: Information technology-Legal aspects